1990
DOI: 10.1111/j.1471-4159.1990.tb13296.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Kynurenine into Rat Brain Slices

Abstract: The transport of [3H]kynurenine ([3H]KYN) into slices from rat tissue was examined in vitro. Brain accumulated KYN seven to eight times more effectively than any of several peripheral organs. Of all the organs tested, only the brain exhibited a sodium-dependent component of the uptake process. After an incubation period of 1 h, sodium-dependent transport amounted to 60% of total uptake. Both processes were abolished by prior sonication of the tissue and significantly inhibited by inclusion of metabolic blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 32 publications
2
47
0
1
Order By: Relevance
“…The poor bioavailability of this compound, and of its more potent congeners, such as 5,7-Cl 2 -KYNA, however has stimulated attempts to identify new agents with greater CNS access and therapeutic action. 3 The potential for a prodrug approach to address this problem is based on the knowledge that, first, L-KYN, the precursor of KYNA, can gain ready access to brain via the large neutral amino acid transporter of the blood-brain barrier 6 and brain cell membranes 13 and, second, that the brain has the metabolic machinery to convert L-KYN as well as its halogenated analogs to KYNA derivatives via the enzyme kynurenine aminotransferase. 9 The L system transporter is fairly loose in its requirements for substrate binding and transfer, 5,7 and it is not surprising that both 4-Cl-KYN and 4,6-Cl 2 -KYN show some affinity for the transport carrier.…”
Section: Discussionmentioning
confidence: 99%
“…The poor bioavailability of this compound, and of its more potent congeners, such as 5,7-Cl 2 -KYNA, however has stimulated attempts to identify new agents with greater CNS access and therapeutic action. 3 The potential for a prodrug approach to address this problem is based on the knowledge that, first, L-KYN, the precursor of KYNA, can gain ready access to brain via the large neutral amino acid transporter of the blood-brain barrier 6 and brain cell membranes 13 and, second, that the brain has the metabolic machinery to convert L-KYN as well as its halogenated analogs to KYNA derivatives via the enzyme kynurenine aminotransferase. 9 The L system transporter is fairly loose in its requirements for substrate binding and transfer, 5,7 and it is not surprising that both 4-Cl-KYN and 4,6-Cl 2 -KYN show some affinity for the transport carrier.…”
Section: Discussionmentioning
confidence: 99%
“…This does not rule out a significant role for de novo synthesis for acute regeneration of NAD. Further investigations are required to established whether extracellular supplies of kynurenine, which is actively taken up by glial cells (Speciale and Schwarcz, 1990), or other tryptophan metabolites can be converted efficiently to the pyridine nucleotide under conditions of acute NAD depletion.…”
Section: Figmentioning
confidence: 99%
“…In in vitro studies using a human heart extract, an increase of L-KYN Baran/Staniek/Kepplinger/Gille/Stolze/ Nohl concentration from 2 Ìmol/l to 3 mmol/l in the incubation medium at pHs between 7.4 and 9.6 induced an elevation of KYNA formation up to approximately 800-fold [10]. At least in the brain L-KYN is actively accumulated by both astrocytes and neurons [11]. Although a major part of KYNA, the transamination product of L-KYN, is rapidly released from the cell [12], it has been suggested that KYNA is to some extent stored in the cell [13].…”
Section: L-kynurenine (L-kyn) Is a Major Intermediate In The Oxidativmentioning
confidence: 99%